Kinetics and Mechanistic study of Saponification of a Few Industrially Important Esters, viz., glyceryl Dilaurate and Glyceryl Oleostearate - Madhava Rao, B.; Gajanna, K. (Asian Journal of Chemistry, 2010)
Kinetics of saponification of two structurally related and industrially important diesters have been investigated. Time ratio method and Swain's standard data for series first order reactions have.been utilised for evaluation of rate data and thermodynamic parameters, viz., ΔE≠ ,- ΔH≠ , ΔG≠, ΔS≠ and log A for both the steps which involve the competitive and consecutive saponification reactions which also indicate that the first step of saponification process is quite faster than the second step and further more the oleostearate is less saponifiable than dilaurate in 72% dioxane-water, DMSO-water moiety and in general these processes are much faster in DMSO-water system than alcohol-water, acetone-water and dioxane-water systems.